Urban Populism and Politics (Study on Public Space Governance in Pangkalpinang City) - Naddya Desteni (Eduvest - Journal of Universal Studies, 2021)
Physical development of public spaces was one of the priority programs during the Molen-Sopian administration as Mayor and Deputy Mayor of Pangkalpinang for the period 2018-2023. The availability of public space in urban areas refers to the provisions for the distribution of the proportion of Green Open Space (RTH), namely 20% Public Green Open Space (RTH) and 10% Private Green Open Space (RTH). The City Government of Pangkalpinang is faced with the dynamics of urban politics which are colored by pros and cons issues related to the development of public spaces in Pangkalpinang City. This study aims to determine the role of the Pangkalpinang City government in striving for the arrangement and management of public space in the Pangkalpinang City area as well as exploring the factors that influence the implementation process. The research method used is descriptive qualitative. The results of this study indicate that the availability of public space in the form of Green Open Space (RTH) in Pangkalpinang City has not reached the minimum target required in accordance with the Regional Spatial Plan (RTRW), which is 20% of the city area. The role of the Pangkalpinang City government in striving for the arrangement and management of public spaces in Pangkalpinang City includes regulators, facilitators, executors and dynamists. In the process of structuring and managing this public space, there are also three factors that influence, namely political will, the role of third parties, and budget availability.